Pengaruh Penggunaan Artificial Intelligence Dalam Pembentukan Peraturan Perundang-Undangan - Mariska Cahyani Putri; Annisa Febyanti; Saskia Azzahra; Nurul Amaliyah Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This writing aims to examine the position and influence of the presence of Artificial Intelligence in the formation of legislation as well as the crucial role of implementing the use of Artificial Intelligence in legislative processes. The research method employed by the author is normative juridical research using data collection techniques through document studies on secondary data. The results of this writing indicate that Artificial Intelligence is a form of progress that can assist and simplify human work. However, its use must be limited by specific regulations to regulate and minimize potential threats or negative impacts. Additionally, Artificial Intelligence is limited to being a tool or supporting assistant in the legislative process. If Artificial Intelligence were to be considered a subject capable of shaping legislation, it would be nearly impossible to implement. This is due to legislation being rules derived from norms that evolve in society and are dynamic. In the end, Artificial Intelligence remains limited to providing assistance to human beings. And the realization of the use of Artificial Intelligence in the realm of law has occurred in Indonesia as well as other countries such as Singapore, China, Estonia and also the United States. These countries have utilized Artificial Intelligence in the realm of law, especially in its use as a tool for the formation of legislation.